1998
DOI: 10.1021/jp982952l
|View full text |Cite
|
Sign up to set email alerts
|

Adlayer Structures of Chlorine, Bromine, and Iodine on Cu(111) Electrode in Solution:  In-Situ STM and ex-Situ LEED Studies

Abstract: Adlayer structures of Cl, Br, and I on the Cu(111) surface have been investigated using in-situ scanning tunneling microscopy (STM) in solution and ex-situ low-energy electron diffraction (LEED) in ultrahigh vacuum. The atomic structure of Cu(111)−(1 × 1) was observed by in-situ STM in a perchloric acid solution. Complementary use of LEED and in-situ STM revealed (p × √3) centered-rectangular phases for Cl and Br, in which the structures are compressed almost linearly with potential. In the case of iodine mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 32 publications
6
81
0
Order By: Relevance
“…Iodine adsorption on Cu (1 1 1) and Cu(1 0 0) LEED [8,9] and STM studies [10] have reported the formation of a ð ffiffi ffi…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine adsorption on Cu (1 1 1) and Cu(1 0 0) LEED [8,9] and STM studies [10] have reported the formation of a ð ffiffi ffi…”
Section: Methodsmentioning
confidence: 99%
“…The adsorption of atomic iodine on Cu(1 1 1) and Cu(1 0 0) has been studied in a number of previous experiments [7][8][9][10][11][12][13][14]. We discuss the details of these previous studies below by comparing the results of our DFT calculations with the experimental observations.…”
Section: Introductionmentioning
confidence: 96%
“…This surface exposes four high symmetry binding sites for adsorption: on-top, bridging, and the fcc and hcp threefold hollow sites. Iodine is known to adsorb in the fcc sites and to form a ð ffiffi ffi 3 p  ffiffi ffi 3 p ÞR30°ordered overlayer at a coverage of 0.33 monolayers (ML) [6][7][8]. The Cu(2 2 1) surface consists of (1 1 1) terraces separated by straight step edges with (1 1 0) structure ( Fig.…”
Section: Comparison Of Co Adsorption On Low and High Miller Index Pt mentioning
confidence: 99%
“…In Ref. [7], iodine was adsorbed on the surface by applying KI solutions to the Cu surface electrochemically. In Ref.…”
Section: Ethyl Iodide On Cu(1 1 1)mentioning
confidence: 99%
“…25 -27 The XPS studies of monolayer coverages of iodine on Pd emersed from aqueous solution indicate that iodine is in a zerovalent state. 24 In situ scanning tunneling microscopy (STM) studies 25 of halide adsorption on Cu(111) indicate that adsorbed species have radii appropriate to zero-valent oxidation states. Chlorine adsorbed on Ag surfaces acts as a siteblocker to H 2 O dissociation under ultrahigh vacuum (UHV) conditions, 26 which suggests a similar zero-valent state.…”
Section: Introductionmentioning
confidence: 99%